An offline Practicum Workshop as An Aid for Students’ Chemistry Laboratory Practical Skills: A Case Study - Kristianto, Hans; Gandajaya, Linda; Simanjorang, Lisbet Warty; Saptasari, Heny (JURNAL PENDIDIKAN SAINS (JPS), 2023)
The COVID-19 pandemic has caused disruption in various sectors including education. Since it was announced for the first time in mid-March 2020 in Indonesia, teaching and learning activities have been carried out online, either synchronously or asynchronously. If ordinary lecture activities still allow the delivery of material by changing forms and media, practicum activities in the chemistry laboratory are completely impossible to carry out and replaced with various forms of virtual learning. This study focuses on evaluating the perceptions of students' practical skills in various basic skills after returning to offline activities, and implementing practicum workshop activities as a corrective effort to improve student skills. Based on the results obtained, students have a low perception of skills, namely in the range 2.56 ± 1.02 to 3.42 ± 1.16 on a scale of 6.00. It can be seen that the effectiveness of virtual practicum is low in terms of skills and there is a need for corrective action so that students can catch up on the basic skills of practice in the chemistry laboratory. After the workshop activities, there was a significant increase (p < 0.05) in students' perceptions of skills with a range of 4.87 ± 0.66 to 5.26 ± 0.73 on a scale of 6.00. Based on the results in this study, it is suggested that other study programs to map and evaluate students' practical skills after the COVID-19 pandemic and take corrective measure to ensure the attainment of practical skills learning outcome.